Trace metals distributions in coastal sea ice of Terra Nova Bay, Ross Sea, Antarctica - GROTTI, MARCO; SOGGIA, FRANCESCO; IANNI, MARIA CARMELA; FRACHE, ROBERTO (Antarctic Science, 2005)
In an attempt to clarify the release of trace elements from the seasonal coastal sea ice, samples were periodically collected in a nearshore station inside the Gerlache Inlet (Terra Nova Bay, Western Ross Sea), during the summer 2000/01 and analysed for dissolved and particulate cadmium, copper, iron, manganese and lead, as well as salinity, suspended particulate matter, nutrients and phytoplankton pigments. In order to provide insight on the metal association with the particles included in the sea ice, the metal solid speciation was also investigated. Both vertical distributions within the ice cores and temporal variations at the seawater interface were studied, in an effort to fully characterize the system and correlation among the considered parameters. Concentrations and speciation patterns clearly indicate metal incorporation within the annual sea ice due to resuspension of sediments, followed by release of particulate metals during melting as a primary process affecting trace metal availability in the Antarctic coastal waters.